HUKUM PIDANA MATI DI INDONESIA BERDASARKAN PERSPEKTIF HAK ASASI MANUSIA DAN ALTERNATIF PENEGAKAN HUKUM: Studi Kasus: Pidana Mati Ferdy Sambo - Cahyani, Gisella Tiara; Sholehah, Siti Bilkis; Salsabillah, Dara Nurul; Ramadhana, Muhammad Alwan; Pratama, Revand Arya; Antoni, Herli (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2023)
Law is a tool for regulating the lives of society, characterized by its coercive and obligatory nature to follow existing rules. Law is created for the benefit of the general public and contains norms of life as a guide for social interaction. The death penalty is the most severe punishment in terms of sanctions for extraordinary criminal offenses such as narcotics, premeditated murder, terrorism, and crimes against national security. However, the implementation of the death penalty in Indonesia has become controversial due to its violation of Human Rights (HR) and the right to life guaranteed by Article 28A, paragraph (1) of the 1945 Constitution. Despite the recent updates in the latest Criminal Code (KUHP) that introduce a probation period of 10 years, pros and cons continue to arise regarding the application of the death penalty. Various perspectives on the death penalty exist, with some considering human rights and principles of justice. Nevertheless, the death penalty must be applied with caution and in consideration of human rights